Práticas colaborativas para solução de conflitos: o modelo descrito pela International Academy of Collaborative Professionals - Del Bel, Iane Naia de Oliveira Ruggiero (2020)
This paper aims to identify the minimum elements and foundations of Collaborative Practices for Conflict Resolution. There is no universal and definitive model. Nevertheless, the analysis has been done by bibliographic research, including the Ethical Standards of the International Academy of Collaborative Professionals (IACP), the first international association of collaborative conflict resolution professionals. Historically, professionals from different fields around the world have built the Practices collectively and continuously. Collaborative Practices are a voluntary auto-composition dispute resolution process, facilitated by a professional team whose work is limited to consensual conflict resolution. Its minimum elements also include the disclosure of material information on the issue by clients and professionals, good faith negotiation of mutually acceptable solutions and a Participation Agreement that binds parties and professionals. The professional team is composed of one lawyer for each party, besides Mental Health Professionals, Financial Professionals and others, depending on the needs of the parties and the case. This allows an interdisciplinary approach to the conflict, covering legal, emotional, communication and financial aspects. Even though the model is recognized by the withdrawal provision for professionals in the event of litigation, other elements make the Collaborative Practices system functional: (1) professionals' and clients' willingness to engage in the model, strengthened by the "facilitative and client-centered" approach; (2) supporting and trusting relationships between professionals and clients; (3) knowledge and skills of the clients and of the professionals on conflict management, communication, interpersonal skills and non-positional negotiation; and (4) flexible structure for this negotiation process